Young women speak out: healing the selves through narrative therapy - Mazmi Maarof; Ruzy Suliza Hashim; Noraini Md Yusof; Raihanah Mohd Mydin (Penerbit UKM, 2012)
This paper explicates the contemporary voices of Malaysian women projected towards raising awareness on violence to the public through Young Women Speak Out, an anthology of short stories and poems written by victims of violence and sexual abuse. This collection is published in 2007 by All Women’s Action Society (AWAM), an independent feminist organisation committed to improving the lives of women in Malaysia. The writers’ writings of life-narratives are analysed in the framework of narrative therapy developed by Michael White and David Epston and Kamsler’s theory of revising individuals’ relationship with one-self in relation to violence and abuse. By placing the plots of the stories within Kamsler’s stages of revising individual’s relationship with one-self in relation to violence and abuse, the stories reflect the authors’ success in forming a more positive self-dignity, thus allowing them to go on with their lives guided by new perspectives and hopes. By contextualizing their violent experiences in a broader cultural politics of race, gender, class, sexuality, professional and institutional dominance, these stories, when viewed as therapeutic engagement, have helped these women to externalise their problems allowing them to create awareness as well as speaking out to the Malaysian society in order to expose the detrimental effects of sexual and domestic violence.